2020
DOI: 10.3389/fneur.2020.00956
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Anosmia: The Olfactory Pathway Hypothesis and Early Intervention

Abstract: Anosmia is a well-described symptom of Corona Virus Disease 2019 (COVID-19). Several respiratory viruses are able to cause post-viral olfactory dysfunction, suggesting a sensorineural damage. Since the olfactory bulb is considered an immunological organ contributing to prevent the invasion of viruses, it could have a role in host defense. The inflammatory products locally released in COVID-19, leading to a local damage and causing olfactory loss, simultaneously may interfere with the viral spread into the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 79 publications
0
48
0
1
Order By: Relevance
“…From recent reports, Italian pediatric cases (between 0 and 19 years of age) amounted to 518,057, corresponding to 14.1% of all the affected population, with 22 pediatric deaths. SARS-CoV-2 infection in children is less common, often spreads within family clusters, and manifests with mild and varied symptoms [ 4 , 5 ] such as fever, nasal congestion, cough, dyspnea, myalgia, arthralgia, headache, gastrointestinal, and skin manifestations with the characteristic anosmia and ageusia [ 6 , 7 ]. Rare cases have shown severe respiratory symptoms requiring intensive care or a multisystem inflammatory syndrome (MIS-C) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…From recent reports, Italian pediatric cases (between 0 and 19 years of age) amounted to 518,057, corresponding to 14.1% of all the affected population, with 22 pediatric deaths. SARS-CoV-2 infection in children is less common, often spreads within family clusters, and manifests with mild and varied symptoms [ 4 , 5 ] such as fever, nasal congestion, cough, dyspnea, myalgia, arthralgia, headache, gastrointestinal, and skin manifestations with the characteristic anosmia and ageusia [ 6 , 7 ]. Rare cases have shown severe respiratory symptoms requiring intensive care or a multisystem inflammatory syndrome (MIS-C) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is clinical evidence that some individuals infected with SARS-CoV-2 experience a loss of smell and taste(23). Furthermore, it has been found that olfactory receptors may be an alternative SARS-CoV-2 entry into the local host cells, which may lead to its spread into the central nervous system(24).…”
Section: Resultsmentioning
confidence: 99%
“…Interaction of vitamin A with olfactory function SARS-CoV2 causes olfactory and/or gustatory dysfunctions in COVID-19 patients (92)(93)(94)(95) . A recent meta-analysis of eight studies confirmed that patients with COVID-19 had significantly higher risks of developing olfactory and/or gustatory dysfunctions compared with normal subjects (OR of 65•9) or patients with acute respiratory infection without detectable virus (OR of 11•3) (94) .…”
mentioning
confidence: 99%
“…The mean time from olfactory loss to recovery onset was reported as 12 d, with complete olfactory recovery in only 51 % of patients (93) . Viral infections are a common cause of olfactory dysfunction (96) , although the pathogenesis of sensory loss after viral infections is not well characterised (92,95) . It is assumed that the nasal epithelium and olfactory bulb could be critical in the pathological development of COVID-19, with mild outcomes of COVID-19 leading to localised effects with mild effects on olfactory function.…”
mentioning
confidence: 99%
See 1 more Smart Citation